Dental biofilm, gingivitis and interleukin-1 adjacent to approximal sites of a bonded ceramic - Katarina Konradsson (Blackwell Synergy, 2007)
Aim: The aim of this study was to investigate in vivo the influence of aged, resinbonded, ceramic restorations on approximal dental biofilm formation and gingival inflammatory response, associated with and without customary oral hygiene. Material and Methods: In a cross-sectional and in a 10-day experimental gingivitis study, Quigley–Hein plaque index, gingival index (GI), crevicular fluid and its levels of interleukin (IL)-1a, -1b and receptor antagonist were measured at appoximal surfaces of leucite-reinforced bonded ceramic coverages, resin composite restorations and enamel and compared intra-individually in 17 participants. Results: No differences were found between the ceramic, composite and enamel regarding plaque index, GI, levels of IL-1a, -1b and the receptor antagonist. Throughout, higher crevicular fluid amounts were observed at ceramic sites compared with the enamel (po0.05). In the experimental gingivitis, plaque index, GI, crevicular fluid and its IL-1a levels increased significantly. Conclusion: The need for optimal oral hygiene and professional preventive oral health care does not seem to be reduced with regard to approximal surfaces of aged, resin-bonded, leucite-reinforced ceramic restorations in comparison with those of a hybrid, resin composite and enamel.